Determining the composition of bacterial community and relative abundance of specific antibiotics resistance genes via thermophilic anaerobic digestion of sewage sludge. (September 2020) - Shin, Jingyeong; Rhee, Chaeyoung; Shin, Juhee; Min Jang, Hyun; Gu Shin, Seung; Mo Kim, Young
Graphical abstract: Highlights: Fates of ARGs and intI 1 from thermophilic AD of sewage sludge were investigated. Thermophilic AD removed ARGs and intI 1 effectively. Erm B decreased significantly, even though removal efficiency of tet A was low. VGT helped shape the development of ARGs. Abstract: In this study, the effects of different temperature transitions on the dynamics of antibiotic resistance genes (ARGs) and bacterial community were investigated during start-up of thermophilic anaerobic digestion (AD) of sewage sludge. Although two thermophilic reactors showed dissimilar removal efficiencies of ARGs in batch mode, both the removal efficiency and reduction patterns of ARGs were similar in continuous stirred tank reactor (CSTR) mode, resulting in significant reduction of the total sum of the relative abundance of ARGs. Using network analysis to explore the correlation between bacterial community and some specific ARGs revealed that composition of the bacterial community played a vital role in the fluctuations in the relative abundance of the antibiotic resistome, demonstrating that shaping the development of ARGs was facilitated by vertical gene transfer. To facilitate eliminating ARGs, minimizing their hosts which persist even under long-term operations is vital in thermophilic AD.